Macrophage subsets in the adipose tissue could be modified by sex and the reproductive age of women. Issue 1 (July 2015) - Králová Lesná, Ivana; Poledne, Rudolf; Fronek, Jiri; Králová, Anna; Sekerková, Alena; Thieme, Filip; Pitha, Jan
Abstract: The presence of proinflammatory monocytes/macrophages (CD14+CD16+) has been documented in conditions of inflammation, such as atherosclerosis. We analysed the proportion of proinflammatory monocytes/macrophages in perirenal and perivascular fat in healthy living kidney donors with regard to sex and age reflecting reproductive status in women; therefore, women were further divided to younger and older group (younger and older than 51 years) reflecting potential age of menopause. Monocyte/macrophages were identified as CD14+ mononuclear cells and divided into subpopulations based on the co-expression of CD16. We found no differences in the monocyte/macrophage content between men (n = 15) and women (n = 28). Conversely, we observed a higher proportion of double positive CD14+CD16+ monocytes/macrophages in older women (n = 14) compared to younger women (n = 14). In addition, a strong correlation was found between the monocyte/macrophage content in fat and age only in older women. Therefore, proinflammatory monocytes/macrophages (CD14+CD16+) should be evaluated according to the sex and age. Highlights: We analysed proinflammatory monocytes/macrophages in perirenal and perivascular fat. We found no differences in the monocyte/macrophage content between men and women. The highest proportion of double positive CD14+CD16+ cells was found in older women. Correlation of monocyte/macrophage content with age was found only in older women. CD14+CD16+ monocytes/macrophages should be evaluated according to the sex and age.